(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Due to increased consumption of resources, especially energy it was necessary to find alternatives characterized by the same quality as well as being of less expensive, and most important of these alternatives are characterized by waste and the fact that humancannot stop consumption. So we have consideredwaste as an alternative and cheap economic resources and by using environmental index the MIP (input materials per unit ,unit / service) is based on the grounds that the product is not the end of itselfit is a product to meet the need of a product or service, awarded a resource input and output within the five basic elements are the raw materials is ecological, Raw materials ecological, water, air and soil erosion for agriculture and forestry, and assuming that waste is a cheap alternative available for some of the natural resources and on the basis of this assumption was calculated material inputs per unit (service / product) and calculating the extent of their impact on the environment when the re-use of waste, because the results were positive and were less than half the rate of other resources used in the production of industrial goods. This helps to show the financial potential of the positive projects in the preservation of natural resources, or to find an alternative have the possibility of achieving the best use and less expensive, and can use this indicator on the corporate level or at the level of society or the state as a whole or a comparison between the different countries, which achieves a statement productive resources the level of the economy of the state as a whole.